Wisdom in Israel - von Rad, Gerhard, 1901-1971; Martin, James D. Dr. (London, UK SCM, 1972)
Includes bibliographical references and indexes.
Originally published in Germans : Weisheit in Israel.-- Neukirchen-Vluyn : Neukirchener-Verlag, 1970
Keywords: Bible. O.T. -- theology